To divide the polynomial \(8x^3 + 20x^2 - 12x\) by \(x + 3\) using long division, follow these steps:
-
Divide the leading term of the dividend by the leading term of the divisor: \[ \frac{8x^3}{x} = 8x^2 \]
-
Multiply \(8x^2\) by the entire divisor \(x + 3\): \[ 8x^2 \cdot (x + 3) = 8x^3 + 24x^2 \]
-
Subtract this result from the original polynomial: \[ (8x^3 + 20x^2 - 12x) - (8x^3 + 24x^2) = -4x^2 - 12x \]
-
Bring down any remaining terms (in this case, none), and repeat the division:
- Now divide the leading term \(-4x^2\) by \(x\): \[ \frac{-4x^2}{x} = -4x \]
-
Multiply \(-4x\) by \(x + 3\): \[ -4x \cdot (x + 3) = -4x^2 - 12x \]
-
Subtract this from \(-4x^2 - 12x\): \[ (-4x^2 - 12x) - (-4x^2 - 12x) = 0 \]
Since the remainder is 0, we can conclude that the polynomial \(8x^3 + 20x^2 - 12x\) divides perfectly by \(x + 3\).
The quotient of the division is: \[ 8x^2 - 4x \]
Now, comparing this result to your options:
- Option #1: \(8x^2 + 44x - 144\) → Not correct
- Option #2: \(8x^2 - 4x\) → Correct!
- Option #3: \(8x^2 - 4x + \frac{12}{x+3}\) → Not appropriate
- Option #4: \(8x^2 + 44x + \frac{120}{x+3}\) → Not correct
Thus, the correct answer is Option #2: \(8x^2 - 4x\).